Community-based approaches to foreign language education - Comber, Barbara (Colombian Applied Linguistics Journal, 2018)
Learning how to recognise and make student and community assets the subject of curriculum is at the core of teachers’ designs and enactments of critical and inclusive pedagogies. However, this era of globalisation and standardisation, where education is increasingly seen as a commodity that underscores economic competitiveness, has made space for local knowledge production, hard to find. Knowing how to incorporate community problems in school-based student-led inquiries, whilst meeting authorised learning outcomes, is also challenging. At the same time there are particular pressures on language teachers where states extol the benefits of English, or another foreign language literacy for global competitiveness. Yet, educational researchers and teacher educators know the potential power of working with students’ assets and motivations to enhance language and literacy learning in classrooms. Community based approaches to language education in various places in Latin America are explored in this issue with contributions from teacher-researchers, collaborative teams, teacher educators and university-based researchers.